IMPLEMENTASI KONSEP KEMANUSIAAN DAN TOLERANSI PADA AJARAN AGAMA SIKH DAN KORELASINYA TERHADAP AJARAN AGAMA ISLAM - rijal muttaqin, Sahrul; abdan fauzi, Rizal; ridwan abdul azis, Muhammad; arridlo, Fikri; Sobirin (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
This study aims to examine the concept of humanity in the sikh religion and identify its correlation with islamic teachings. Using the inter-religious comparative analysis method, the author compares the principles of humanity upheld by both religions. The Sikh religion,rooted in the spiritual traditions of India , teaches the concept of seva ( selfless service ) and calls for the defense of truth and justice. Through the study of their holy book, the Guru Granth Sahib, whose principles encourage devotion to fellow human beings and provide high respect for human beings. In islamic teachings,human values are reflected in the concept of ukhuwah ( brotherhood ) and the principle of rahmatan lil alamin ( mercy to the universe ) by referring to the source of islamic religious guidance, namely the Qur’an and Hadith, through Islamic teachings that emphasize the importance of empathy and social justice towards all God’s creations without exception and living in harmony with fellow humans. Through this comparative analysis, the author higlights the similarities and differences in the concept of humanity in sikhism & islam, the author also sees the potential for interfaith correkation and understanding to stregthen human values in the midst of current global challenges, especially in the unitary state of the Republic of Indonesia. It is hoped that this article can provide insight and understanding of the humanitarian aspects through the perspectives of the sikh religion and islam, it is hoped that it can stimulate interfaith dialogue that can fister a sense of humanity Keywords: Humanity, corelation, Islam